Analysis Of The Determinants Of Resilience To Food Insecurity In An Arid Environment: The Case Of Small-Scale Farmers In The Souss Valley In South-Central Morocco - EL JARARI, Mustapha; EL MORCHID, Brahim (Research Collaboration Community (RCC), 2024)
Climate change is affecting food security in Morocco, particularly for small farmers in arid and semi-arid zones like the Souss valley. Principal component analysis of the FAO's four pillars of resilience RIMA-II model has enabled us to narrow down the important data for each pillar. Six components are considered as predictors of household food security, and their contribution is significant at the p